Understanding by Design (UbD) Model in Mathematics Teaching and its Impact on Students - Gürbüz, Özge; Yurtseven, Nihal (International Electronic Journal of Elementary Education, 2026)
The purpose of this study was to examine the impact of Understanding by Design (UbD)model in mathematics teaching on students' creative thinking skills, cognitive flexibility, and learning retention. Employing a pre-test post-test control group quasi-experimental design, the study involved 40 seventh-grade students, with 20 in the experimental group and 20 in the control group, attending a public school in Istanbul, Türkiye. While mathematics lessons were conducted using unit plans developed with the UbD instructional design model in the experimental group, no changes were made to the teaching approach in the control group. Data collection tools included the Torrance Creative Thinking Test, Cognitive Flexibility Scale, and a mathematics follow-up test. Data analysis involved Mann-Whitney U Test and Wilcoxon Signed Ranks Test. The results revealed a significant difference favoring the experimental group in terms of creative thinking skills, cognitive flexibility, and learning retention. These results suggest that UbD model in teaching plans can serve as valuable tools in enhancing creative thinking, cognitive flexibility, and learning retention. Keywords: Understanding by design, creative thinking, cognitive flexibility, learning retention.